Interpreting the marketization of employment services in Great Britain and Denmark. (December 2014) - Larsen, Flemming; Wright, Sharon
Marketization is an important component of international shifts in the governance of employment services. Despite contrasting underlying welfare systems and employment services of different scales and character, both Denmark and Great Britain were distinct from many other comparable countries in contracting out employment services in the late-1990s. By comparing the starting positions and divergent trajectories of marketization in these two very different welfare systems, we see some common traits in how it so far has been difficult to make marketization deliver on its promises. We find in both cases difficulties for the contracted-employment services to reduce bureaucracy, save money through innovation, realize user choice, prevent poor quality services or increase efficiency/effectiveness through better job outcomes. Instead we find, paradoxically, that the market could not operate without re-regulation. In the absence of the intended effects, we furthermore question why policymakers in such different socio-political contexts continued to support the marketization strategy. The explanation is found in combination with wider governance and policy shifts, which have contributed towards altering the governance mix to reposition key actors and interests in ways that would have otherwise been contested.